A New Opportunity Related Hypercholesterolemic and the Improvement of Glucose Levels, Lipid Profiles, and Microbial Activity: Red Dragon Fruit (Hylocereus polyrhizus) Peel Yogurt and Animal Study - Putriningtyas, Natalia Desy; Cahyati, Widya Hary; Kusuma, Refani Alycia; Nugraheni, Kartika; Nisa, Alfiana Ainun (Unnes Journal of Public Health, 2024)
Hypercholesterolemia estimated to cause 2.6 million deaths and 29.7 million disability problems.The incidence of Noncommunicable diseases (NCD) such as coronary heart disease (CHD), type2 diabetes, and some types of cancer can be involved with hypercholesterolemiaed. Red dragonfruit (Hylocereus polyrhizus) peel contains total phenolic compounds, flavonoids and dietary fiber.Red dragon fruit (Hylocereus polyrhizus) peel, which was originally considered as trash can beused to produce yogurt. This study aimed to analyse the effect of red dragon fruit (Hylocereuspolyrhizus) peel yogurt on levels of fasting blood glucose, lipid profile and microbial activity inhypercholesterolemic Wistar rats. This was an experimental- research with pre and post-test control group design. A total of 25 male Wistar rats were divided into five groups randomly. Hypercholesterolemic conditions in the Wistar rats were obtained from consuming solution consisted of 1% of cholesterol powder and 0.5% of cholic acid for 14 days. Each Wistar rats received 20 g/day standard feed. The grouping were Group 1 (negative control group); Group 2 (hypercholesterolemic group); Group 3 (1.8 ml/kg b.wt/day of dragon fruit peel yogurt); Group 4 (2.7 ml/kg b.wt/day of dragon fruit peel yogurt); Group 5 (3.6 ml/kg b.wt/day of dragon fruit peel yogurt). The intervention was performed for 28 days. Blood glucose levels and lipid profiles weremeasured before and after the intervention. Blood glucose, lipid profiles and microbial activity weremeasured using GOD-PAP, automatic biochemistry analyser and pour plate method respectively.Data were analysed using paired t test and one-way ANOVA. Blood glucose, TC, LDL-C, TGlevels were decreased, and the other side HDL-C was increased significantly in the Group dragonfruit peel. There was no difference in the total number of microbes in all groups. Dragon fruit peelyogurt is effective in improving glucose levels and lipid profile of hypercholesterolemic Wistar rats.